Influence of osmotic dehydration on ascorbic acid loss in pickled dry peppers (Capsicum chinense) - Silva, Tissiane Mayara da; Argandoña, Eliana Janet Sanjinez; Madrona, Grasiele Scaramal; Moraes, Izabel Cristina Freitas; Haminiuk, Charles Windson Isidoro; Branco, Ivanise Guilherme [UNESP] (Brazilian Archives of Biology and Technology, 2012)
The objective of this work was (1) to develop a dehydrated pepper with 45% humidity, determining the drying curves for pepper, with and without osmotic pre-treatment and (2) to evaluate the influence of both drying and osmotic treatment on the content ascorbic acid (vitamin C) in fresh pepper and pepper with 45% humidity. The experiments were carried out using the peppers cut in half, with and without osmotic pre-treatment, followed by drying in an oven at 70 ºC. The results showed that the osmotic pretreatment did not influence the retention of ascorbic acid during the drying of pepper. The sensory analysis regarding the color, flavor, and texture attributes revealed that there was no difference in the acceptability.
Keywords: Capsicum chinense; ascorbic acid; osmotic dehydration; drying